Physical and Chemical Macroscopic Processes in Wooden Construction Materials of Buildings during WUI Fires: Recent and Advanced Developments; Processes; Vol. 10, iss. 2 - Baranovskiy N. V. Nikolay Viktorovich (2022, 2022)
Title screen